Manoeuvrability assessement of a hybrid compound helicopter configuration - Ferguson, K.; Thomson, D. (My University, 2014)
The compound helicopter design could potentially satisfy the new emerging requirements placed on the next generation of rotorcraft. The main benefit of the compound helicopter is its ability to reach speeds that significantly surpass the conventional helicopter. However, it is possible that the compound helicopter design can provide additional benefits in terms of manoeuvrability. The paper features a conventional helicopter and a hybrid compound helicopter. The conventional helicopter features a standard helicopter design with a main rotor providing the propulsive and lifting forces, whereas a tail rotor, mounted at the rear of the aircraft provides the yaw control. The compound helicopter configuration, known as the hybrid compound helicopter, features both wing and thrust compounding. The wing offloads the main rotor at high speeds whereas two propellers provide additional axial thrust as well as yaw control. This study investigates the manoeuvrability of these two helicopter configurations using inverse simulation. The results predict that a hybrid compound helicopter configuration is capable of attaining greater load factors that its conventional counterpart, when flying a pullup-pushover manoeuvre. In terms of the Accel-Decel manoeuvre, the two helicopter configurations are capable of completing the manoeuvre in comparable time-scales. However, the addition of thrust compounding to the compound helicopter design reduces the pitch attitude required throughout the acceleration stage of the manoeuvre.